Study on coloration of Monascus-nata complex using combination of rice flour, tofu solid waste, and rice bran extracts as the medium - TIAS HESTI KUSUMAWATI; SURANTO SURANTO; RATNA SETYANINGSIH (Biodiversitas Journal of Biological Diversity, 2005)
Monascus-nata complex was made up from fermented nata which was grown in the medium containing Monascus purpureus fungi, that could be used as coloration of nata. Rice flour usually used as medium to produce pigments by M. purpureus. Tofu solid waste and rice bran could be used to produce pigments although the colour intensity of M. purpureus pigment was lower than rice. The aims of these research were to study colour, pH medium and weight of miselium Monascus-nata complex from the combination of rice flour with tofu solid waste extracts and rice flour with rice bran extracts as the medium. In these research, 5% (b/v) rice flour extracts, combination of rice flour extract : tofu solid waste extract in the ratio of 1:1, 1:2, 1:3 and rice flour : rice bran extracts in the ratio of 1:1, 1:2, 1:3 were used as the medium. Ten nata de coco (1x1x1 cm3) were put in to the extracts of medium (100mL) in bottle, then inoculated with 10% (v/v) starter of M. purpureus containing 1.3x107 cfu/mL and incubated at room temperature on an orbital shaker at 100 rpm for 16 days. Parameters which were measured, i.e. colour intensity, preferable test, pH medium, weight of miselium Monascus-nata complex. Data were analyzed using analysis of variant and followed by DMRT in 5% significations except preferable test which were analyzed using hedonic test. Combination of rice flour extract : tofu solid waste extracts in the ratio of 1:1 could be used to replace rice flour extracts on the making of Monascus-nata complex. Orange colour intensity from rice flour extract : tofu solid waste extracts in the ratio of 1:1 was higher than from rice flour extracts. Orange colour intensity from rice flour extract : tofu solid waste extracts in the ratio of 1:1 and rice flour were 0.156 and 0.123 respectively. Red colour intensity from medium rice flour extract : tofu solid waste extracts in the ratio of 1:1 approach the red colour intensity of rice flour. Red colour intensity from medium rice flour extract : tofu solid waste extracts in the ratio of 1:1 and rice flour extract were 0.088 and 0.145 respectively. All of pH value decreased from 7 to 6.82. Weight of miselium Monascus-nata complex from all medium was average 0.024 g. Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: Monascus-nata complex, rice flour, tofu solid waste, rice bran